Rituximab in the treatment of three coexistent neurological autoimmune diseases: chronic inflammatory demyelinating polyradiculoneuropathy, Morvan syndrome and myasthenia gravis. Issue 2 (12th May 2010) - Sadnicka, Anna; Reilly, Mary M; Mummery, Cath; Brandner, Sebastian; Hirsch, Nicholas; Lunn, Michael P T
Abstract : A 76-year-old man with a pre-existing diagnosis of myasthenia gravis was admitted to an intensive care unit with pneumonia and type II respiratory failure. In addition, muscle weakness, widespread myokymia, neuropsychiatric disturbance and autonomic disturbance were present. Antivoltage gated potassium channel antibodies, antistriated muscle antibodies and antiacetylcholine receptor antibodies were positive. Nerve-conduction studies demonstrated findings consistent with patchy demyelination. Electromyography confirmed widespread myokymia, and there was evidence of diffuse encephalopathy on electroencephalography. Diagnoses of Morvan syndrome and chronic inflammatory demyelinating polyradiculopathy (CIDP) were made. Treatment with intravenous immunoglobulin, plasma exchange and high-dose steroids were ineffective, and the patient remained dependent on mechanical ventilation. The coexistence of possibly three humorally mediated autoimmune diseases led to treatment with rituximab. Rituximab treatment was followed by an improvement in muscle strength, allowing successful weaning from mechanical ventilation, diminution in myokymia and improved cognition. At follow-up, there was reversal of the neuropsychiatric manifestations and normal muscle strength. This case suggests that rituximab may be useful in the treatment of autoimmune neurological disease refractory to other immunosuppressant therapies. Specifically, it adds further evidence for the use of rituximab in CIDP. As indications for rituximab in humorally mediated disease continue to expand, international multicentre randomised controlled trials are required to prove the effectiveness of this important emerging biological agent.